Analysis of Dynamic Parameters of the System of Raster Formation and Control - Antanas Fursenko; Arturas Kilikevicius; Kristina Kilikeviciene; Jonas Skeivalas; Albinas Kasparaitis; Jonas Matijosius; Dariusz Wieckowski (Communications - Scientific letters of the University of Zilina, 2020)
The presented research work analyzes the sensing system, the main aim of which is a raster formation and controlling this process using the optical measuring equipment and high precision angle encoders. Optical measuring equipment are used for the raster position detection, meanwhile angle encoders for controlling the tape speed. The main parameter of raster formation process is fixed transportation speed, but there are difficulties to realize it, because there is imperfection of the device elements. The article analyzes the dispersion of vibration accelerations of the raster formation device and tape in the two directions (transverse and longitudinal) and presents an analysis of their parameters in application of the theory of covariance functions. The results of the measurements of vibration accelerations at the fixed points of the device constructions and the tape were recorded on a time scale in the form of digital arrays (matrices). Values of auto-covariance and inter-covariance functions of digital arrays of the vibration accelerations measurement data were calculated by changing the quantum interval in a time scale. The developed software Matlab 7 in operator package environment was used in the calculations.